Focus on Brazil: Country images held by Malaysian learners of Brazilian Portuguese - Nikitina, L.; Furuoka, F. (Unisinos, 2014)
This study explores images about Brazil held by learners of Brazilian Portuguese in a big public university in Malaysia. It employs a mixed methods approach for this purpose. In the qualitative component of the study, the students’ images about Brazil were explored by analyzing their responses to an open-ended question and grouping the resultant images into categories. In the quantitative strand, favourability of the images about Brazil was assessed using the ratings that each respondent had assigned to his or her images about Brazil. The findings revealed that references to football and sporting events made up the largest share in the kaleidoscope of images about Brazil. For the most part, the students’ images about the target language country, culture and people were highly positive. At the same time, the findings indicated that the students’ mental pictures about Brazil were limited to popularly held country stereotypes. The article concludes with a discussion on pedagogical implications of the findings.